Accuracy of Traditional and Modern Formulas for Intraocular Lens Power Calculation After Radial Keratotomy Using Standard Keratometry - Helaly HA; Elhady AM; Elnaggar OR (Clinical Ophthalmology, 2023)
Hany Ahmed Helaly, Amr Mohamed Elhady, Osama Ramadan Elnaggar Ophthalmology Department, Faculty of Medicine, Alexandria University, Alexandria, EgyptCorrespondence: Hany Ahmed Helaly, Ophthalmology Department, Faculty of Medicine, Alexandria University, 30 Roshdy Street, Roshdy, Alexandria, Egypt, Tel +201225466733, Email hany209209@yahoo.comPurpose: To compare the accuracy of multiple traditional and modern intraocular lens (IOL) power calculation formulas in post-radial keratotomy (RK) patients undergoing cataract surgery.Methods: This retrospective case series included 50 eyes with prior RK who underwent routine phacoemulsification surgery with single-piece acrylic IOL implantation (A constant = 118.8). Outcomes of multiple formulas were calculated. Included formulas were SRK/T, Holladay 1, Holladay 2, Haigis, Barrett True-K, Haigis and Barrett True-K (target refraction of 0.50 D), Barrett Universal II, Kane, PEARL-DGS, Shammas no history, DK SRK/T, DK SRK/T (target refraction of 0.50 D), Double K (DK) Holladay 1, and DK Holladay 1 (target refraction of 0.50 D). Averages of multiple combinations of best-performing single formulas were calculated. Primary outcome is mean absolute error (MAE).Results: Haigis (with − 0.50 D target refraction) and DK SRK/T showed the lowest mean and median absolute errors (MedAE) followed by Haigis, Barrett True-K, and Barrett True-K (with − 0.50 D target refraction). Combinations of 3, 4, or 5 of best performing single formulas yielded good results with > 60% of cases within +0.50 D of intended refraction and MAE around 0.50 D. The best performing formulas with flatter K readings were PEARL-DGS and Haigis (with additional − 0.50 D target refraction) with MAE of 0.72 + 0.71 D and 0.70 + 0.70 D, respectively, followed by Barrett True-K (with intended − 0.50 D target refraction) with MAE of 0.75 + 0.63 D.Conclusion: Using an average of three or more Haigis (with − 0.50 D target refraction), the Barrett True-K, DK Holladay 1, and DK SRK/T formulas showed better outcomes than using a single formula for IOLMaster 700 standard K readings. The PEARL-DGS formula showed better accuracy in eyes with flatter K readings (< 38 D).Keywords: radial keratotomy, IOL calculation, PEARL-DGS, Barrett True-K, DK Holladay 1, DK SRK/T